Evaluation of Monocular Treatment for Meibomian Gland Dysfunction with an Automated Thermodynamic System in Elderly Chinese Patients: A Contralateral Eye Study - Yinying Zhao; Jialu Xie; Junhua Li; Yana Fu; Xiaolei Lin; Shangrong Wang; Jiling Ma; Yune Zhao (Journal of Ophthalmology)
Purpose. To investigate the safety and efficacy of monocular treatment for elderly Chinese patients with meibomian gland dysfunction (MGD) with an automated thermodynamic system. Methods. This study was a prospective, examiner-masked, contralateral eye clinical trial. The eye perceived by the patient to be worse (test eye) received a 12-minute LipiFlow treatment, while the other eye served as control. All patients were examined before treatment and one week, one month, and three months after treatment. Clinical parameters included dry eye symptoms, lipid layer thickness (LLT), partial blink (PB) ratio, invasive tear breakup time (ITBUT) and cornea staining, Schirmer I test, meibomian glands yielding liquid secretion (MGYLS), and meibomian gland dropout. Results. A total of 29 patients were examined during the three-month follow-up. At each posttreatment visit, they had a significant reduction in dry eye symptoms accompanied by an increase of ITBUT and MGYLS and a reduction in corneal staining compared with the baseline parameters. There was a significant improvement in MGYLS and ITBUT in the test eye compared with the control eye. Other clinical parameters were not statistically significant. Conclusion. LipiFlow is an effective treatment for patients with MGD. Monocular treatment with LipiFlow may be a cost-effective treatment option to those afflicted with MGD in the developing world.